Varicella-Zoster Virus Gastritis: Case Report and Review of the Literature. (August 2017) - Nohr, Erik W.; Itani, Doha M.; Andrews, Christopher N.; Kelly, Margaret M.
We report varicella-zoster virus (VZV) gastritis in a 70-year-old woman postchemotherapy for lymphoma, presenting with abdominal pain, vomiting, and delirium without rash. A gastric biopsy demonstrated viral inclusions but posed a diagnostic challenge as immunohistochemistry for cytomegalovirus and herpes simplex virus were negative, and VZV immunohistochemistry was not available. The patient developed a vesicular rash 7 days after her symptoms began. Molecular testing of the gastric biopsy and a skin swab both confirmed VZV infection. She also had probable involvement of her liver and pancreas based on imaging and serum chemistry, and possible central nervous system involvement. She recovered with appropriate antiviral therapy but later developed a postherpetic neuralgia, and chronic intrahepatic biliary strictures; liver biopsy demonstrated a cholangiopathy of uncertain etiology. A literature review of the pathogenesis, epidemiology and sequelae of VZV infection is included.